Raising Environmental Consciousness and Its Impact on Adolescence Interpersonal Dynamics in Wendelin van Draanen's 'Flipped' - Qonita Nowindra Ramadhani; Henrikus Joko Yulianto (Hasanuddin University, 2026)
This study investigates the intricate relationship between environmental identity and adolescence interpersonal dynamics within Wendelin van Draanen's novel